2010
DOI: 10.1111/j.1467-8535.2010.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Student attitudes towards and use of ICT in course study, work and social activity: A technology acceptance model approach

Abstract: The increasing use of information and communication technology (ICT) in higher education has been explored largely in relation to student experience of coursework and university life. Students' lives and experience beyond the university have been largely unexplored. Research into student experience of ICT used a validated modelThe Technology Acceptance Model (TAM) -to explore the influence of work and social/leisure contexts as well as course study, on attitudes towards and take up of technology. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 21 publications
9
144
1
15
Order By: Relevance
“…As an example, JISC (Joint Information Systems Committee) conducted in recent years a wide programme where different projects used mainly qualitative methods to examine the nature of learners' experiences with ICT (Sharpe et al 2005;Conole 2008;Sharpe et al 2009;Edmunds, Thorpe, and Conole 2012). Some important points emerged in relation to the main aim of this research:…”
Section: Approaches To Investigate Students' Experiences With Technolmentioning
confidence: 99%
“…As an example, JISC (Joint Information Systems Committee) conducted in recent years a wide programme where different projects used mainly qualitative methods to examine the nature of learners' experiences with ICT (Sharpe et al 2005;Conole 2008;Sharpe et al 2009;Edmunds, Thorpe, and Conole 2012). Some important points emerged in relation to the main aim of this research:…”
Section: Approaches To Investigate Students' Experiences With Technolmentioning
confidence: 99%
“…The study, using the Technology Acceptance Model, found that attitudes to the technology are influenced by the usefulness and ease of use of the technology. It also highlighted that ICT is perceived most positively in the work environment and technology use at work is a significant driver for technology use in other environments (Edmunds et al, 2012). Furthermore, Heikkinen, Nurminen, Smura, and Hammainen (2012) conducted research with the objective of understanding the behavior of mobile phones users toward energy consumption.…”
Section: Attitudementioning
confidence: 99%
“…A diverse set of studies have been conducted on the area of attitude of users toward ICT's. For instance, Edmunds, Thorpe, and Conole (2012) looked at the attitudes of students toward using ICT's in their studies, work and social environment. The study, using the Technology Acceptance Model, found that attitudes to the technology are influenced by the usefulness and ease of use of the technology.…”
Section: Attitudementioning
confidence: 99%
“…According to the study internet usage and online shopping are most common in the university age 18-30 years old students even though they do not have sufficient funds for shopping but the university students found on the top listed using internet and has great intention towards online shopping (Edmunds et al, 2010). In the developed countries individual intention and behavior of online shopping is widely studied but lack of studies counted in developing country like Malaysia where online shopping is getting popularity among university students.…”
Section: Introductionmentioning
confidence: 99%